From eating identity to authentic selfhood: Identity transformation in eating disorder sufferers following psychotherapy. (28th April 2015) - Cruzat‐Mandich, Claudia; Díaz‐Castrillón, Fernanda; Escobar‐Koch, Tatiana; Simpson, Susan
Abstract: Background: The following article illustrates the development of the identity configuration process of Chilean female patients with an eating disorder (ED) following successful psychotherapeutic treatment. Method: This was a qualitative, descriptive study, which explored patients' subjective perspectives. In‐depth interviews were conducted with 20 female patients, and data were analysed according to procedures established by the Grounded Theory method. Results: Four dimensions of identity were identified: (1) self‐image as idealised versus imperfect; (2) knowledge of one's inner world; (3) impulse control; and (4) life goals. Transcending these themes was the central notion of identity and a shift in this identity from someone who defines themselves by their eating disorder toward a more authentic and complex sense of self. Conclusion: Results suggest that successful treatment facilitates the construction of an authentic identity, which includes developing a more realistic and complex understanding of themselves and their emotional and physical needs. Abstract :